A God of Vengeance and of Reward? Voters and Accountability. Issue 1 (30th October 2018) - Griffin, John D.; Newman, Brian; Nickerson, David W.
Abstract: Theories of democratic politics prize congruence between citizens' preferences and their elected representatives' actions in office. Elections are a critical means for achieving such policy congruence, providing voters the opportunity to chasten representatives who are out of step with constituent preferences and to reward the faithful. Do voters act this way? Recent studies based on observational data find they do, but these data are somewhat limited. We employ a survey experiment to estimate the extent to which information about policy congruence affects voters' evaluations of representatives. We informed some subjects how often their member of Congress's voting decisions match their own stated preferences on the same policies. We find that information about congruence enhances accountability by affecting constituent evaluations of representatives and may also affect citizens' propensity to participate in upcoming elections.